Effect of a two-week beta-alanine supplementation on plasma carnosine and lactic acid in trained-wrestlers - Rashidlamir, A.; Bagheri, R.; Akbari, M. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
PURPOSE: Some studies have reported that -alanine supplementation can increase high-intensity intermittent exercise performance and training adaptations. In this study, we investigated the effect of -alanine on lactate acid and carnosine in trained wrestlers. METHODS: 19 trained-wrestlers (mean age ± SD 22.52±2.31 yrs. height173.38 ± 4.86 cm, weight 76.22 ± 9.07 kg) participated in this design and randomly divided into supplementation (s) and placebo (P) groups. S group consumed 1000 mg -alanine and P group consumed placebo for 2 weeks. Blood samples were taken, before the first and 6 minutes after the last HIIT test for detection of plasma lactate and carnosine. SPSS software and independent t-test method were used for analyzing data (p<0.05). RESULTS: The S group, taking -alanine, showed a significant decrease in lactic acid (p=0.00) and a significant increase in carnosine plasma (p=0.02), While these changes weren`t observed in the P group. CONCLUSION: According to the results, -alanine supplementation for 2 weeks may be associated with increase buffering system via an increase in carnosine and decrease lactic acid during high-intensity interval training in wrestlers. We recommend that -alanine supplementation may be useful for wrestling athletes.